Relación entre los ingresos y los gastos de la zona registral n° IV – sede Iquitos periodo 2017 - 2021 - Salas Barrera, Clara Rosa (2023)
The National Superintendency of Public Registries (SUNARP) is the State entity in charge of registering and publicizing acts of natural or legal persons; therefore, it is required that public funds be allocated for the acquisition of sophisticated computer systems, which help to improve the registration process as well as strengthen the registration activities among others; Therefore, the study has the purpose of determining the relationship between the income and the expenses of the Registry Zone No. IV; Headquarters Iquitos, during the period 2017 - 2021. In this sense, a Descriptive investigation, Correlational level and Non-Experimental design is established, concluding that there is a linear relationship between the Income Captured and the Accrued Expenses of the Registry Zone No. IV – Iquitos Headquarters, during the aforementioned five-year period, likewise, the value of the Correlation coefficient (R) has been r = 0.990428505; being a value very close to 1; On the other hand, the Determination Coefficient (R2) has been R2 = 0.980948624; also close to 1; Therefore, there is a relationship and determination between Expenses (dependent variable) and Income (independent variable). In this sense, according to the regression analysis that was carried out and having the positive value of the parameter (b_1) ̂, it is determines the direct relationship between the Income and Expenses of the Registration Area No. IV; Headquarters Iquitos during the analysis period, that is, if the independent variable (Income) increases, then the dependent variable (Expenses) increases.